Peran Epistemologi Filsafat Al-Hikmah Al-Muta'aliyah Bagi Kesadaran Eksistensi Spiritual - Mohammad Eka Yulianto; Arqom Kuswanjono; Agus Himawan Utomo (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
The purpose of this study is to find a way to achieve awareness of spiritual existence through the role of epistemology in the Al-Hikmah Al-Muta'aliyah school of philosophy. This study uses a qualitative descriptive literature method based on literature data from books, journals and comparisons to previous studies. The results of the study indicate that epistemology is a fundamental aspect of knowledge that underlies all science and perspectives on the world showing the connection of knowledge to existence and spirituality, which in fact cannot be separated or particularized or secularized. The conclusion of this study shows that placing epistemology as an aspect of science can be introduced early on to be able to foster awareness of spiritual existence as a fundamental foundation that goes beyond the limitations of interpretation in the form of religious doctrines and the limitations of particular science and influenced by secularism, so that it can form humans in a complete awareness and ready to face modernity and globalization that reduces human nature. Keywords: Al-Hikmah AlMuta’aliyah, Epistemology, Existential, Mulla Sadra, Spiritual